The various various concepts of Algebra in the context of Mathematics Education - Lima, Maria Vanísia Mendonça de; Borges Neto, Hermínio (Educação Matemática Debate, 2023)
This study is part of an ongoing doctoral research by the Postgraduate Program in Education at the Federal University of Ceará. It aims to present the conceptions of Algebra in the field of Mathematics Education and our own conceptions about this area. To develop it, we initially carried out a Systematic Literature Review in order to identify the conceptions of Algebra in publications. Subsequently, we carried out a theoretical study to describe the existing categories of Algebra conceptions and formulate our own understandings. The results of the study indicate that there are categorizations of Algebra conceptions already established by several authors, with the prevailing idea that this area of ​​Mathematics consists of: arithmetic generalization, problem-solving tool, relationships between quantities, symbolic language and set of algorithm techniques, among other understandings.